Culture/Community/Race: Chinese Gay Men and the Politics of Identity - Kapac, Jack (Anthropologica, 2022)
"Culture/Community/Race" is an ethnographic account of the development of gay identities and correlative collective practices among a group of Chinese men in Toronto in the 1980s. The cultural and racial politics of these identities/practices are explored through an examination of the role of Chinese "culture" in their development and through a discussion of the sexual politics of race among gay men. This latter material addresses the sexual meanings of racial difference and the politicization of these meanings among Chinese gay men.